Pentingnya motivasi belajar dalam meningkatkan hasil belajar siswa - azzahroh, almas aulia (Maliki Interdisciplinary Journal, 2025)
I raised this title with the aim of understanding the meaning of motivation. Motivation "is an internal desire to encourage someone to take action to achieve goals, in an educational context, in the learning process, trying to understand the material, and achieving good learning outcomes. Motivation can be obtained from various sources, such as internal, curiosity and external from factors outside the individual such as the environment. " Motivation is an important factor that influences students' success in learning. Someone will feel satisfied with their learning results if they have the encouragement or desire to continue learning. Motivation functions as the main driver to achieve good results. Students will be more active and enthusiastic in carrying out learning activities if they are driven by strong motivation. With high motivation, it is hoped that students can achieve maximum learning outcomes. Motivation also plays an important role in creating discipline and persistence in learning. Without strong motivation, a student tends to give up easily when facing difficulties or challenges in the learning process. Therefore, it is important for educators to create an environment that can trigger student motivation so that they are motivated to continue trying and do not give up easily. Thus, motivation is not only a driving factor, but also a key element in maintaining student enthusiasm and consistency in learning, which in turn contributes to their academic achievement.